Pemanfaatan Kacang Mete Sisa Sortir Sebagai Mentega Kacang Dengan Perbedaan Metode Pengeringan Dan Konsentrasi Minyak - Lewerissa, Karina Bianca; Mawarno, Binardo Adiseno; Mawarno, Binardo Adiseno; Lestari, Mentari Wahyu; Lestari, Mentari Wahyu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 4 (2022): Jurnal ITEPA, 2023)
Cashew nuts are one of the most popular foodstuffs and have a fairly high selling value. However, the high or low selling value of cashews is influenced by the quality of the raw materials.  In general, whole form cashew nuts have a high selling value.  On the other hand, cashew nuts left over from sorting which are not whole/broken have low selling value.  The purpose of this research is to make butter from broken (second grade) cashew nuts.  In this study, cashew butter was made by two different treatments, namely: drying methods (roast and oven) and different concentrations of oil, i.e (7,5%, 10%, 12.5%, and 15%).  The physicochemical properties of the product were tested by proximate analysis, viscosity test, and organoleptic test.  The results showed that the drying method affected the moisture content and color of the product.  The oil concentrations affect the fat content, aroma, taste, and texture of the product.  The best product is obtained by using roasted method with 7.5% oil.  The resulting product has a pale brown color, strong nutty aroma, a savory taste, and a dense texture.